PENGARUH PENAMBAHANAN METAKAOLIN DAN SUPERPLASTICIZER TERHADAP KUAT TEKAN BETON PADA MUTU K-400 - A Rivai, Masri; Martini, RA Sri; Dimas, Erdin (Universitas Muhammadiyah Palembang, 2021)
High-quality concrete usually uses an addition to workaholic, high-pressure, and concrete durability such as metacaolin and superplasticizer.The Study was conducted to find out how the metacaolin + superplasticizer addition to the strong K-400 press of concrete. The test object used was a cube 15 x 15 x 15 cm. Strong tests of concrete were made at the age of 3 days, 14 days, and 28 days. The research is done on normal concrete, and metacaolin 10% + superplasticizer 0,5%, 1%, 1,5%, 2%, 2,5%, 3%, and 3,5% with separate parts.Research shows the strong value of normal concrete pressure at 28 days on 403,66 Kg/cm² while strong value of optimum concrete at 28 days occurs in a variety of Metacaolin 10% + Superplastizer 3% on 460,58 Kg/cm². It is known that adding metacaolin + superplasticizer add to strong concrete pressure.Key Words : concrete, metacaolin, superplasticizer, and strong press.